Assessment of soft tissue facial profile, nasal airway morphology and dental arch features in adult malay obstructive sleep apnea patients using geometric morphometric analysis - Hamid, Suzina Sheikh Ab (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
a serious public health problem. The objectives of this study were to localize and quantify the differences in facial soft tissue profile, nasal airway morphology and dental arch features in adults Malay with and without OSA using geometric morphometric analysis. One hundred and twenty adult Malays aged 18-65 years (mean± SD, 33.2 ± 13.31) were divided into two groups of 60. Both OSA and control groups undergone clinical examination and limited channel polysomnography. Only 108 subjects (54 in each group) were able to complete facial soft tissue imaging, acoustic rhinometry (AR) measurements, and upper and lower dental impression. Nine facial soft tissue and 25 upper and lower study models homologous landmarks were digitized using MorphoStudio software to obtain the x, y, z coordinates. The minimal cross section l(MCAl) and minimal cross sectional2 (MCA2) were also obtained from AR. The mean OSA and control were computed, and subjected to t-test and geometric morphometric analysis. The mean body mass index was found to be significantly greater for the OSA group (33.2kg/m2 ± 6.5) when compared to the control group (22.7 kg/m2 ± 3.5 p < 0.001). The mean neck size was also greater for the OSA group (43.6cm ± 6.02) compared to the control group (22.7cm ± 3.52, p < 0.001). Using geometric morphometric analysis, significant differences were found in facial soft tissue profile between the two groups. These differences were localized in the bucco-submandibular regions of the face predominantly, with inter-landmark distances indicating an increase in size of7-22% in OSA groups (p < 0.05). For nasal airway morphology, the mean MCA1 and MCA2 on the AR graph were found to be significantly smaller in the OSA group than control group (p < 0.001). Using geometric morphometric analysis on AR data, significant differences were found in nasal airway morphology between the two groups . Specifically, the mean nasal airway were significantly narrower in OSA groups with decreased in size ("'10-22%) appears in nasal valve I head of inferior turbinate area predominantly. For dental arch features, the mean upper and lower OSA dental arch morphologies were significantly narrower in widths with an increase in upper and lower dental arch length when compared with control subjects (p < 0.05). Specifically, the mean OSA configuration of the upper arch was 7-11% narrower in the transverse plane in the incisor and canine regions compared to the control configuration, and inter-landmark analysis confi1med this finding. For the lower arch, the mean OSA configuration was lOll% narrower in the premolar and molar regions. In conclusion, there were clearly definable differences in the facial soft tissues profile, nasal airway morphology and dental arch features when comparing patients with OSA to controls, with obesity acting as an additional risk factor in this particular group of Malay patients. These differences need to be recognized since they can improve our understanding of etiological basis of OSA disorder, facilitate the limited availability of diagnostic setup, and provide valuable screening information in the identification of patients with undiagnosed OS A.